Biosensors, biofeedback, and neurofeedback - Monteiro, Pedro (2022)
In this chapter, the authors write about the processes of biofeedback, giving an insight about the sensors that might be used, the overall concept of biofeedback, as well as the evidence regarding the effectiveness of neurofeedback for the treatment of mental disorders.The main goal is to provide those introducing to the biofeedback as a self-regulation technique, used now for more than 50 years, with concise information about the sensors that might be used to detect the most common measured responses, the main types of physiological biofeedback, and the state-of-the-art evidence about neurofeedback as a form of brain training for individuals with the most prevalent mental disorders. Biofeedback and neurofeedback are guided therapies that include a vast and rowing variety of methodologies aimed to return information to the individual, regarding the physiological functions of the organism itself, in order to enable the modification of those otherwise considered unconscious physiological responses, designed to improve the individual’s health and wellness